A versenytilalmi megállapodás - Ember, Alex (Debreceni Jogi Műhely, 2015)
The “agreement on non-competition” is essentially the extension of the protection of the basic economic interest of the employer. While during the employment relationship several labor law provisions protect the interest of both parties, the “agreement on non-competition” is designed to protect the employer’s interests after the termination of the relationship. This means – in return for financial compensation – the former employee needs to refrain from any kind of business competition against his/her former employer. This necessarily involves financial compensation and may have several restrictions, such business or geographical area or time. The previous Labor Code did not specify for detailed regulation of the issue and the law remained rather vague. It merely referred to the fact that parties – based on their own free will – may enter into such agreement. However the new Labor Code contains explicit regulations under title XVIII of the Act as “Particular Agreements Related to Employment”. The “agreement on non-competition” belongs to the field of employment law. Unlike the previous Labor Code that categorized this possible agreement as of purely civil law in nature, the new Labor Code declares it to belong under the scope of the Labor Code. The previous regulation even ordered the provisions of the Civil Code to be applied to such agreements however the new legislation brought a conceptual change. The currently effective regulation provides for a 2-year limitation on such conduct on the employee’s part that would create competition with the employer. The exact amount of the consideration payable for this obligation remains to be decided by the parties however the Labor Code suggests that it shall be based on how difficult the applied restrictions make it for the employee to find another job with his qualifications and experience. As a basic limit the law provides that the amount shall not be less than one-third of the base wage payable for the same period of time. The “agreement on non-competition” is not to be confused with similar legal institutions. The paper points out two close similarities in the legal system. One being the employee’s obligation of confidentiality; this prevails after termination of the employment relationship as well without any time or similar restrictions and even without any financial compensation. The other one is the so called “non-compete” agreement from the field of competition law. This is applicable after takeovers where the seller shall refrain from engaging into business in the same area as the buyer. In the field of labor law the time period for the “agreement on non-competition” is up to the agreement of the parties however the new law invokes an upper limit of two years that is following the termination of the employment relationship. This is a decrease from the previous regulation that provided for a period of three years. The agreement can be modified by the consent of both parties just like the employment contract or civil law agreements. In case of violation of the agreement three cases are to be analyzed. The first is the case of the employee breaching the provisions of the contract. In this case the employee is liable for damages towards his/her former employer. The provisions of the new Civil Code and those of the Labor Code are to be applied to the damages. In the second case the employer may request an injunction to prohibit the employee from any conduct breaching the agreement while the third case involves the breach of the agreement on the employee’s part for which the rules of the Civil Code and the Labor Code are to be applied as well.